IMPROVING THE SYSTEM FOR ASSESSING THE EFFICIENCY OF CORPORATE GOVERNANCE IN UZBEKISTAN - Kayumov Ravshan Ismailovich (Journal Park Publishing, 2023)
The article assesses the current state of assessment of the corporate governance system, reveals its shortcomings, namely, that the questionnaire prepared for these purposes has not changed since its development, many issues in it concerned the introduction of corporate governance, which has now lost relevance. In addition, the questionnaire is not aimed at achieving the goals and objectives for the development of corporate governance established by law. The author gives proposals for amendments and additions to eliminate the shortcomings in the questionnaire
Keywords: corporate governance, questionnaire for assessing the corporate governance system, performance evaluation, key indicators, supervisory board.